Recent advance in carrot genomics - Iorizzo, Massimo (2017)
In recent years there has been an effort towards the development of genomicresources in carrot. The number of available sequences for carrot in publicdatabases has increased recently. This has allowed the design of SSRs markers,COS markers and a high-throughput SNP assays for genotyping. Additionalmolecular tools include the first high-throughput DArT array and the fullsequence of organelle genomes. These molecular resources have been successfullyused to gain new insights into carrot genetic diversity, organelle genomeevolution and to establish the first dense sequence-based linkage maps. Supported by a consortium of private companies, sequencing of the carrot genomeis currently ongoing. Its release, will establish a solid framework for carrotgenomic studies, opening a new challenging and exciting era for the carrot scientific community.